L'ESS une Opportunité de Transformation Soclétale Face Aux Vulnérabilltés Aggravées par la Crise Sanitaire - Smadi, Amina; Abrika, Belaid (جامعة سطيف 1 - كلية العلوم الاقتصادية والتجارية وعلوم التسيير, 2020)
The article deals with the issue of the socioeconomic impact of Covid19 in Algeria. Its objective is to highlight the influence of the crisis on social vulnerabilities regenerating ancestral solidarity practices. The vulnerabilities approach is approached in interaction with resilience allowing societies to recover from crises by relying on new strategies. In this context, the article poses the problem of the institutionalization of the social and solidarity economy by adopting it as a medium-long term strategy in order to contain the crisis. The methodological approach is eminently analytical and synthetic-deductive. We conclude with the immediacy of a resilient policy around the social and solidarity economy sector and to start a process of formalization of the informal sector reducing vulnerabilities.
Keywords: الاقتصاد الاجتماعي -- الأزمات الصحية -- فيروس كورونا "كوفيد-19"